Purification and anticholinesterase sensitivity of cholinesterase extracted from liver tissue of Puntius javanicus - Sabullah M.K.; Abd. Shukor M.Y.; Shamaan N.A.; Khalid A.; Ganzau A.J.; Sulaiman M.R.; Jirangon H.; Ahmad S.A. (Friends Science Publishers, 2024)
Indexed by WOS/ Scopus